REVISITING LIFE INSURANCE IN ISLAMIC LAW - K. M. Zakir Hossain SHALIM (Türkiye İslam İktisadı Dergisi)
Life insurance can provide individuals with an important financial planning tool through which they can obtain financial security for their families and businesses as the prime objective of life insurance is undertaking a responsibility towards safeguarding widows, orphans and other dependents of the deceased (assured / policyholder) from unexpected future material risks. However, it is not surprising that until now throughout the Muslim world the burning question of the day is whether life insurance is permissible or not? Indeed, a heated controversy has been raging over this problem, and Muslim jurists are divided into two groups on this issue. Some hold it permissible with certain conditions that should be imposed on it; and others reject it without considering any condition for its permissibility. Interestingly, both groups have supported their views, according to their understanding of the proofs and sources of Islamic law, which have created much confusion in the Muslim world. Hence, this article intends to re-examine the concept of life insurance and different views of Muslim jurists on this issue, in order to determine the preferable view in this regard.